Using patient-reported outcome measures to assess the effectiveness of social media networking programs for people living with overweight and obesity to adopt a healthier lifestyle - Saadi, Alend; Fellrath, Jean-Marc; Bec-Moussally, Joanna; Papastathi-Boureau, Chrysoula; Blanc, Céline; Courtine, Valentin; Vanini, Léo; Marechal, Marc; Authier, Florence; Curty, Bertrand; Fournier, Pierre; Diana, Michele; et al. (Frontiers in Public Health, 2023)
Introduction Overweight, obesity, and their associated health complications have become a major public health issue. Online approaches have been rarely attempted to address the problem. The aim of this study was to evaluate the effectiveness of using social media networking for people living with overweight and obesity to adopt a healthier lifestyle with a three-month multidisciplinary healthcare program. Effectiveness was assessed through questionnaires on patient-related outcome measures (PROMs). Materials and methods Two non-profit associations designed the program delivered to people living with overweight and obesity in a closed group via Facebook, the popular social network. The three-month program had three main axes, namely nutrition, psychology, and physical activity. Anthropomorphic data and sociodemographic profiles were collected. Quality of life (QoL) was assessed at the beginning and at the end of the intervention using PROM questionnaires for six different domains, i.e., body image, eating behavior, physical, sexual, social, and psychological functioning. Results Six hundred and twenty persons participated in the program; 567 persons consented for the study, and 145 completed the questionnaires entirely. QoL was significantly improved in five out of six domains, i.e., body image, eating behavior, as well as physical, sexual, and psychological functioning. The improvement was valid regardless of age, gender, initial body mass index, person with or without children, educational level (primary versus secondary versus high school), and occupation (employment compared to unemployment or any kind of social assistance). In multivariate analysis, living as a couple was an independent factor correlated to a positive progression in four domains, i.e., body image, eating behavior, as well as physical, and psychological functioning. Conclusion This study showed that an online lifestyle intervention might be a promising way of improving the quality of life of people living with overweight or obesity.